Autophagy defects suggested by low levels of autophagy activator MAP1S and high levels of autophagy inhibitor LRPPRC predict poor prognosis of prostate cancer patients. Issue 10 (7th July 2014) - Jiang, Xianhan; Zhong, Weide; Huang, Hai; He, Huichan; Jiang, Funeng; Chen, Yanru; Yue, Fei; Zou, Jing; Li, Xun; He, Yongzhong; You, Pan; Yang, Weiqiang; et al.
Abstract : MAP1S (originally named C19ORF5) is a widely distributed homolog of neuronal‐specific MAP1A and MAP1B, and bridges autophagic components with microtubules and mitochondria to affect autophagosomal biogenesis and degradation. Mitochondrion‐associated protein LRPPRC functions as an inhibitor for autophagy initiation to protect mitochondria from autophagy degradation. MAP1S and LRPPRC interact with each other and may collaboratively regulate autophagy although the underlying mechanism is yet unknown. Previously, we have reported that LRPPRC levels serve as a prognosis marker of patients with prostate adenocarcinomas (PCA), and that patients with high LRPPRC levels survive a shorter period after surgery than those with low levels of LRPPRC. MAP1S levels are elevated in diethylnitrosamine‐induced hepatocelular carcinomas in wildtype mice and the exposed MAP1S‐deficient mice develop more malignant hepatocellular carcinomas. We performed immunochemical analysis to evaluate the co‐relationship among the levels of MAP1S, LRPPRC, P62, and γ‐H2AX. Samples were collected from wildtype and prostate‐specific PTEN‐deficient mice, 111 patients with PCA who had been followed up for 10 years and 38 patients with benign prostate hyperplasia enrolled in hospitals in Guangzhou, China. The levels of MAP1S were generally elevated so the MAP1S‐mediated autophagy was activated in PCA developed in either PTEN‐deficient mice or patients than their respective benign tumors. The MAP1S levels among patients with PCA vary dramatically, and patients with low MAP1S levels survive a shorter period than those with high MAP1S levels. Levels of MAP1S in collaboration with levels of LRPPRC can serve as markers for prognosis of prostate cancer patients. © 2014 Wiley Periodicals, Inc.